Metodological issues in measuring the detection of emotional disorders by primary care physicians: a review of the literature Metodologias utilizadas para detectar distúrbios emocionais em clínicas de assistência primária à saúde: revisão de literatura - Eduardo Iacoponi (Universidade de São Paulo, 1988)
A series of studies in the field of Epidemiological Psychiatry have been performed over the last two decades, and these have focused on the ability of primary care physicians to detect emotional disorders in the patients that attend their practices. The scientific methodology utilized in these studies is the subject of this review, which contains a discussion concerning: a) interviewer awareness bias; b) accuracy of the instruments and c) medical and psychological concepts involved in defining minor emotional disorders. Suggestions for change in the methodology are made in each of the sections of the review. Na área de epidemiologia psiquiátrica vêm sendo realizados, nos últimos vinte anos, estudos que têm como finalidade medir a habilidade que clínicos gerais possuem em detectar distúrbios emocionais nos pacientes que procuram atendimento na rede básica de saúde. A metodologia utilizada nesses estudos é o tema central da atual revisão, que contém a) viés do entrevistador; b) acuidade dos instrumentos; e c) conceitos médicos e psicológicos envolvidos na definição de distúrbio psiquiátrico menor. São também apresentadas sugestões para mudanças de metodologia.